Preparation of Business for Expansion to Chinese Market - Fučikovský, Jan; Strouhal, Jiří, 1980-; Rott, Martin; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2016)
This master thesis is written as a guideline for successful business expansion to Chinese market. It describes the regional characteristics, which are important in order to understand the Chinese culture, since without proper understanding of the culture, all of its aspects and concepts such as Guanxi, no foreign firm will be able to succeed in China. Apart of the cultural analysis it also deals with the theory of expansion, how to correctly approach it, what are the possible entry modes and financial sources. I used three case studies, which provide real life experience with this issue from different points of view. The practical part of the thesis is primarily focused on financial industry in China, specifically on investment funds and what should be the necessary steps for any investment fund, which would like to expand to Chinese market.
Vedoucí práce: Jiří Strouhal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses